A Study on Practical Strategies for University Libraries in Serving Industry-Education Integration (Journal of Education, Humanities, and Social Research, 2025)
The evolving landscape of higher education, driven by national strategies such as industry-education integration, necessitates a fundamental shift in the role and ser-vices of university libraries. This paper focuses on the practical strategies and path-ways for libraries to transition from a traditional supportive role to an active participant in this integrated educational model. Rather than presenting isolated tactics, this study proposes a holistic framework where four key dimensions—resource allocation, service integration, platform construction, and evaluation—are systematically inter-connected. The proposed strategies aim to guide university libraries in constructing a modern knowledge service system that effectively supports holistic talent development and contributes to national strategic goals.